A case of Barber‐Say syndrome in a male Japanese newborn. Issue 5 (4th September 2014) - Suga, Kenichi; Shono, Miki; Goji, Aya; Matsuura, Sato; Inoue, Miki; Kawahito, Masami; Kinoshita, Michiyo; Takeda, Misa; Mori, Kazuhiro
<x xml:space="preserve">Abstract</x> We reported a case of Barber‐Say syndrome (BSS) in a Japanese newborn. Distinctive features of BSS were found; macrostomia, gingival dysplasia, cup‐shaped low‐set ears, wrinkling redundant skin and hypertrichosis. Fundus showed subretinal drusenoid deposits, a novel finding of BSS. Genetic analysis is underway using next‐generation genome sequencing and microarray analysis. <boxed-text content-type="graphic" id="ccr3128-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>